Optimising Special Voting Rights in Dual-Class Share Structure Companies: A Corporate Governance Perspective from China - Fan, Ruoshan; Liu , Yuntao; Su, Sanxin (Transformations In Business & Economics, 2026)
China has established a pre-access approval system for companies with dual-class share structures that adopt special voting rights. Due to the overly stringent nature of this approval process, few companies opt for the special voting rights system. This paper examines the application of the special voting rights system and dual-class share structures in Chinese companies, as well as the current status of relevant legal texts. Through normative and comparative analysis, it is found that the strict pre-access regulations for the special voting rights system have led to issues such as the overall design deviating from market innovation goals, information disclosure deficiencies resulting in inefficient information utilisation, and insufficient incentives limiting the role of independent directors. These problems hinder the full mobilisation of continuous innovation enthusiasm in tech-driven enterprises and, in the long term, are detrimental to the modernisation of China’s capital markets. To address these issues, mechanism design theory should be introduced to transform the regulatory model of the special voting rights system, reconstructing it with an incentive-oriented approach while moderately relaxing pre-access controls. By implementing measures such as incentive compatibility, improving information disclosure, optimising the functions of independent directors, and enhancing judicial remedies, a balanced regulatory environment can be created, achieving a dynamic equilibrium between innovation development and the protection of minority shareholders’ interests.
Keywords: dual-class share structure; special voting rights; mechanism design theory; agency costs; incentive compatibility